Ali bin Isa al-Kahhal : pioneer in ophthalmology - Omar, Nurizan; Kabbashi, Nassereldeen Ahmed (IIUM Press, 2011)
This chapter investigates Ali bin Isa AI-Kahhal contribution to ophthalmology especially in eye disease. The main objective of this chapter is to emphasize the influence of AI-Kahhal theory and applications in ophthalmology. The importance of this chapter is to reveal the greatest contribution of Al Kahhal in ophthalmology. The methodology used in doing this chapter is library based research and most of data is collected from a medical journal which is from a reliable source